Factors that contributes the willingness to stay in organisations - Cruz, M.; Dias, Á. L.; Pereira, L. F.; Lopes da Costa, R.; Gonçalves, R. (International Journal of Business Governance and Ethics, 2025)
The competitive context of globalisation is arising some complex issues for companies. One of the main problems is high turnover rates, which are negatively affecting organisations' results. The willingness to stay in a company can be affected by numerous variables and, understanding these variables can be crucial for the sustainability of any business. This research aims to address and measure willingness to stay within a company, understand if and how much it is influenced by organisational culture, specifically by commitment, happiness, justice and loyalty. Using survey data from 284 active workers, the results reveal that willingness to stay is positively influenced by organisational commitment, organisational happiness and, organisational loyalty. Although organisational justice does not directly affect willingness to stay, it acts as a mediator in the other three variables, revealing an indirect relationship between organisational justice and willingness to stay established through organisational commitment, organisational happiness and, organisational loyalty.